Sistem Pendukung Keputusan Pemilihan Jurusan Pada SMK Ymik Joglo Jakarta Barat Menggunakan Metode Simple Additive Weighting (SAW) - Amalia Fitriyani; Rani Irma Handayani; Euis Widanengsih (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2020)
Decision Support System (DSS) is a computer-based system that can be used to help someone improve their performance in decision-making. By using the DSS, are expected to help decision-making in solving problems to determine the majors at SMK YMIK Joglo Jakarta Barat. In this research will be developed using the method of a decision support system that can solve the problem of Fuzzy Multiple Atrribute Decision Making (FMADM) which is proven to have a very effective performance against data whose value is the form of a specific value within the reach range. DSS method used in this research is the Simple Additive Weighting (SAW). This method determines the value weights for each attribute, followed by a process of rankings. So will result in the best alternative of many alternative calculation which is quite appropriate. The alternative a new prospective student there in SMK YMIK Joglo Jakarta Barat which will be selected based on the criteria specified.